2020
DOI: 10.1159/000507189
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Creutzfeldt-Jakob Disease: A Retrospective Analysis of 104 Cases

Abstract: Background: Sporadic Creutzfeldt-Jakob disease (sCJD) is an extremely rare fatal and infectious neurodegenerative brain disorder characterized by rapidly progressive dementia, cerebellar ataxia, and visual disturbances. This article summarizes the retrospective analysis of 104 sCJD patients in the First Medical Center of Chinese PLA General Hospital from 2003 to 2019. Methods: A retrospective analysis of the medical records of the 104 patients diagnosed with sCJD was performed from the aspects of demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
8
16
0
3
Order By: Relevance
“…In this study, we found that there were more female than male sCJD patients, and the female-to-male ratio was 1.39. Two studies of Chinese patients were consistent with our findings, in which the number of females predominated (10,12), but two other studies had reported a higher proportion of males, where the female-to-male ratio was 0.82 and 0.79, respectively (8,14). Because of small sample size and various nationalities in China, there might be biases in those results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we found that there were more female than male sCJD patients, and the female-to-male ratio was 1.39. Two studies of Chinese patients were consistent with our findings, in which the number of females predominated (10,12), but two other studies had reported a higher proportion of males, where the female-to-male ratio was 0.82 and 0.79, respectively (8,14). Because of small sample size and various nationalities in China, there might be biases in those results.…”
Section: Discussionsupporting
confidence: 90%
“…Another two surveys in China have produced results essentially in agreement with ours at the median onset age, which was 64 years in our study (8,11). According to these reported Chinese studies, most of suspected patients were not tested for PRNP gene to rule out genetic Creutzfeldt-Jakob disease (8,9,11,14), which might affect the results and analysis of the study. Similarly, there were two patients younger than 30 years old in our study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a study conducted in the United Kingdom, cerebellar ataxia occurred as the only clinical manifestation in 5% of patients with CJD 25 . In contrast, in a study of Chinese patients with CJD, up to 51.9% of affected individuals presented cerebellar ataxia 26 , which coincides with our findings. Thus, based on our results, we also predict that the genetic and molecular characteristics of the PrP Sc underlying ataxic subtypes of sCJD (VV2 and MV2) may have a high incidence in Mexico.…”
Section: Discussionsupporting
confidence: 91%